2014
DOI: 10.1074/mcp.m114.040923
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Thylakoid Sub-compartments using a Mass Spectrometry-based Approach

Abstract: Photosynthesis has shaped atmospheric and ocean chemistries and probably changed the climate as well, as oxygen is released from water as part of the photosynthetic process. In photosynthetic eukaryotes, this process occurs in the chloroplast, an organelle containing the most abundant biological membrane, the thylakoids. The thylakoids of plants and some green algae are structurally inhomogeneous, consisting of two main domains: the grana, which are piles of membranes gathered by stacking forces, and the strom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
76
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 107 publications
(113 reference statements)
12
76
0
Order By: Relevance
“…In flowering plants, levels of HCF222 mRNA declined by a factor of 5 relative to the maximum expression in apical meristems of 1-d-old seedlings. This is consistent with the proteome study, where HCF222 was measured with only a few counts in chloroplasts from 4-to 5-weekold seedlings (Tomizioli et al, 2014). Together, these observations suggest that HCF222 shows highest expression levels in young leaf stages.…”
Section: Hcf222 Possibly Catalyzes Protein Maturation At the Thylakoidssupporting
confidence: 79%
See 2 more Smart Citations
“…In flowering plants, levels of HCF222 mRNA declined by a factor of 5 relative to the maximum expression in apical meristems of 1-d-old seedlings. This is consistent with the proteome study, where HCF222 was measured with only a few counts in chloroplasts from 4-to 5-weekold seedlings (Tomizioli et al, 2014). Together, these observations suggest that HCF222 shows highest expression levels in young leaf stages.…”
Section: Hcf222 Possibly Catalyzes Protein Maturation At the Thylakoidssupporting
confidence: 79%
“…6 and 7). The localization in chloroplasts is supported by a recent semiquantitative proteome study, where HCF222 was detected for the first time in this cell compartment (Tomizioli et al, 2014). Furthermore, our successful complementation of the knockout mutant with a chloroplast-directed HCF222 strongly suggests that the main site of action of this protein is located to the chloroplast (Table II; Fig.…”
Section: Hcf222 Belongs To a Group Of Dnaj-like Zinc-finger Proteins supporting
confidence: 62%
See 1 more Smart Citation
“…PSA2 was detected in two independent proteomic analyses of thylakoid membranes in Arabidopsis, the latter of which reported its enrichment specifically in non-appressed membranes (28,38). We confirmed that PSA2 is localized to non-appressed membranes by probing immunoblots of leaf extracts, intact chloroplasts, and chloroplast subfractions with the PSA2 antibody (Fig.…”
Section: Arabidopsis and Maize Psa2 Mutants Specifically Lack The Psisupporting
confidence: 62%
“…2B). Consistently, proteomics approaches on thylakoid membranes separated into grana and stroma lamellae identified the Arabidopsis thaliana TEF30 homolog (AT1G55480) exclusively in stroma lamellae (Tomizioli et al, 2014).…”
Section: Tef30 Is a Chloroplast Protein Associated With Psii Monomersmentioning
confidence: 78%